Sustainable Livestock Management Practices: Balancing Production and Environmental Conservation - Yulianti, Utami Agus; Muchtar, Asikin; Amruddin, Amruddin (Riwayat: Educational Journal of History and Humanities, 2024)
Sustainable livestock management practices are increasingly vital in addressing the dual challenges of meeting rising global demand for animal products and minimizing environmental impact. This study employs a qualitative approach using literature review and library research to explore methods that balance livestock production with environmental conservation. The findings reveal that sustainable practices such as rotational grazing, integrated crop-livestock systems, and precision feeding significantly enhance resource efficiency and reduce ecological footprints. Additionally, the implementation of biogas production from manure and improved waste management systems demonstrates potential in mitigating greenhouse gas emissions and soil degradation. Key drivers of adoption include policy support, farmer education, and market incentives, while barriers include financial constraints, lack of technical knowledge, and resistance to change. The study also highlights the role of technological innovations and community-based initiatives in fostering sustainable practices across different socio-economic and ecological contexts. By synthesizing insights from previous research, this paper underscores the importance of collaborative approaches that engage stakeholders at all levels to achieve sustainability in livestock management. The results contribute to the broader discourse on sustainable agriculture, offering practical recommendations for policymakers, farmers, and researchers to promote environmentally friendly livestock systems without compromising productivity. This study emphasizes that achieving the delicate balance between production and conservation requires integrated strategies tailored to local conditions and global sustainability goals.